SARACEN DI MEDIA ONLINE PERIODE AGUSTUS-SEPTEMBER 2017 (ANALISIS FRAMING BERITA EGGI SUDJANA DALAM KELOMPOK SARACEN DI MEDIA INDONESIA.COM DAN OKEZONE.COM) - Erna Diani; Arie Prasetio (Dialektika, 2018)
The Internet has provided various facilities to the public in obtaining and producing information. But with the ease offered by the internet, not infrequently people take advantage of these excellence to the negative thing. Saracen is a group of hate speech spreaders and racial issues arrested by the Police on August 23, 2017. In the Saracen group's arrest report there is Eggi Sudjana's name, a lawyer and activist who allegedly involved in the Saracen as Advisory Council. The purpose of this research is to know the framing of news about the involvement of Eggi Sudjana in Saracen group in online media mediaindonesia.com and okezone.com. This research uses framing analysis of Robert N. Entman with qualitative research method and constructivist paradigm. The results show that mendiaindonesia.com and okezone.com have different views in framing the news. Mediaindonesia.com tends to be neutral and objective in its reporting and frames the involvement of Eggi Sudjana in Saracen group is still an allegation as a fact and informations that comes from the police. While okezone.com tends to be subjective and biased to Eggi Sudjana as seen from the issues that are shown from Eggi Sudjana’s side by emphasizing the fact that Eggi Sudhaja is an innocent person.